2012
DOI: 10.1089/gtmb.2012.0051
|View full text |Cite
|
Sign up to set email alerts
|

Association of TCF7L2 and ADIPOQ with Body Mass Index, Waist–Hip Ratio, and Systolic Blood Pressure in an Endogamous Ethnic Group of India

Abstract: Despite the increasing burden of type 2 diabetes (T2D) and its established association with anthropometric and physiological traits as a risk factor, genetic studies focusing on the association of T2D-related genes with quantitative traits like body mass index (BMI), waist-hip ratio (WHR), and systolic blood pressure (SBP) are only a few for western populations and rare for Indian populations. The present study tested the association of TCF7L2, HHEX, KCNJ11, and ADIPOQ with BMI, SBP, and WHR in men and women o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…Our results are consistent with recent genetic data showing an association between the TCF7L2 rs7903146 variant and increased systolic BP in an endogamous ethnic group from India [36]. However, it should be noted that a recent large genome-wide association study (GWAS) did not report a significant association between the TCF7L2 variant rs7903146 and BP, although a trend was observed for systolic BP (p=0.06) and pulse pressure (p=0.04) [37].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with recent genetic data showing an association between the TCF7L2 rs7903146 variant and increased systolic BP in an endogamous ethnic group from India [36]. However, it should be noted that a recent large genome-wide association study (GWAS) did not report a significant association between the TCF7L2 variant rs7903146 and BP, although a trend was observed for systolic BP (p=0.06) and pulse pressure (p=0.04) [37].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the T risk allele was also associated with a lower body weight, BMI, abdominal circumference and waist-to-hip ratio. This observation has been made in a number of population samples [ 4 , 24 , 26 , 27 ] but contrasts with another study in which the risk allele was associated with higher BMI [ 28 ]. Interestingly, TCF7L2 is expressed in adipose tissue and is involved in Wnt-dependent regulation of adipogenesis [ 29 ].…”
Section: Discussioncontrasting
confidence: 82%
“…However, in the current study, we could not observe significant differences in LDL levels or other lipid fraction between genotypes. Leu et al [29] reported a protective effect of T allele of rs1501299 on blood pressure and Gupta et al [30] showed a reverse effect of T allele in hypertension. These relationships with blood pressure were not detected in our observational study.…”
Section: Discussionmentioning
confidence: 99%